Scientific Learning and Process Skills Mathematics: Comparison and Relationship - Kamid, Kamid; Mujahidawati; Iriani, Dewi; Nawahdani, Ahmad Mansur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Process skills have an important role in the world of education, therefore the process skills of each student need to be improved. This study aims to analyze the comparison of process skills, problem solving models to mathematics, and to analyze the relationship between problem solving models and students' skills in mathematics. This research uses a quasi-experimental quantitative research type. The sample in this study was 288 students. The sampling technique used is purvosive sampling. There are two instruments in this study, namely process skills and problem solving models. The assumption tests carried out in this study were the normality test and linearity test, than continued to test the hypothesis, namely the T test and correlation test. From the results of the process skills T test, there are differences in students' process skills on mathematics subjects. Likewise with the T-test of the problem solving model, there are differences from the model of the student's problem solving learning response to mathematics subjects. As for the results of the correlation test between process skills and problem solving learning models, there is a relationship between process skills and problem solving learning models on mathematics subjects.